2005
DOI: 10.1111/j.1529-8817.2005.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

CLATHROMORPHUM NEREOSTRATUM(CORALLINALES, RHODOPHYTA): THE OLDEST ALGA?1

Abstract: The longevity of organisms is intrinsically interesting and can provide useful information on their population structure and dynamics and the dynamics of associated communities. With the exception of perennial Laminariales that have rings in the stipe, the life spans of most perennial macroalgae are unknown or based on anecdotal observations. Using morphological analyses combined with the location and time of the rise in 14 C from atmospheric nuclear testing within the thallus, we determined that the growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 18 publications
0
31
1
1
Order By: Relevance
“…This carbonate crust (typically 0.5-10 cm thick, but to over 0.5 m in thickness; Lebednik, 1976) is present on all but the most mobile or friable rock surfaces (Frantz et al, 2005;Adey and Hayek, 2011). Because it is a high-magnesium carbonate, laid down mostly by coralline red algae, this crust can be called a cor-strome.…”
Section: The Distribution Of Clathromorphum Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…This carbonate crust (typically 0.5-10 cm thick, but to over 0.5 m in thickness; Lebednik, 1976) is present on all but the most mobile or friable rock surfaces (Frantz et al, 2005;Adey and Hayek, 2011). Because it is a high-magnesium carbonate, laid down mostly by coralline red algae, this crust can be called a cor-strome.…”
Section: The Distribution Of Clathromorphum Speciesmentioning
confidence: 99%
“…As previous studies have demonstrated (Halfar et al, , 2008(Halfar et al, , 2011aFrantz et al, 2005;Hetzinger et al, 2011;Williams et al, 2011), these centuries-old carbonate formations, through analysis of their temperature-and light-dependent growth layers and the trace chemical structure of their carbonate cell walls, can provide significant climate archives. The coralline provides a surface for algal epiphytes, and both the corallines and the epiphytes are grazed by many invertebrates.…”
Section: S M I T H S O N I a N C O N T R I B U T I O N S T O T H E M mentioning
confidence: 99%
“…Seaweeds display widely diverging life history strategies ranging from short-lived ephemeral species to extremely long-lived species, such as Ascophyllum nodosum (Åberg 1992a,b) or certain red algae (crustose red algae: Paine et al 1979;Cryptonemia: Scott et al 1982; coralline algae: Frantz et al 2005) and green algae (e.g. Halimeda, HillisColinvaux 1980).…”
Section: Mortalitymentioning
confidence: 99%
“…as new thalli grow at the surface of the rhodolith bed, older thalli become covered by sediment, die, and form part of the dead deposit. Individual coralline algal thalli can live to at least ~850 years (Frantz et al, 2005) and accumulations of these algal thalli have created maërl deposits spanning the last 20,000 years (Figure 6;Bosence, 1983). unlike most carbonate-depositing organisms, which have a more restricted distribution, coralline algae occur from polar (Schwarz et al, 2005) to tropical (Littler et al, 1991) shallow seas.…”
Section: Rhodoliths As Environmental Recordersmentioning
confidence: 99%
“…δ 18 O in Clathromorphum nereostratum and Lithothamnion glaciale represents ambient seawater temperature at seasonal resolutions and has been used to reconstruct northeastern atlantic sea-surface temperature since 1970 (Halfar et al, 2000(Halfar et al, , 2008. Lithothamnion muellerii and C. nereostratum have been shown to record atmospheric 14 C concentrations (Frantz et al, 2000(Frantz et al, , 2005, which are critical for determining long-term growth rates and age in coralline algae as well as dating the exact timing of climatic events recorded by the growth-banding structure or chemistry within the algae. Overall, coralline algae are ideally suited as chemical environmental recorders because (1) they do not suffer diagenetic effects due to the presence of the living membrane covering the carbonate skeleton (alexandersson, 1974); (2) there is no stress-related geochemical deviation in Mg/Ca-temperature relationships (Kamenos et al, 2008);and, (3) there is no nonequilibrium-associated oxygen isotope fractionation in maërl (Rahimpour-Bonab et al, 1997;Halfar et al, 2007).…”
Section: Rhodoliths As Environmental Recordersmentioning
confidence: 99%